Some Characteristics of Permafrost and Its Distribution in the Gaize Area on the Qinghai—Tibet Plateau, China. Issue 2 (1st May 2016) - Chen, Ji; Zhao, Lin; Sheng, Yu; Li, Jing; Wu, Xiao-dong; Du, Er-ji; Liu, Guang-yue; Pang, Qiang-qiang
ABSTRACT: An investigation of permafrost in the Gaize area in the west Qinghai—Tibet Plateau in China was conducted in October and November of 2010 and 2011. It was found that mean annual ground temperature was >−1 °C with a permafrost thickness of <60 m in the widespread alpine steppe below an altitude of 5400 m a.s.l. The active layer thickness was usually deeper than 3 m with a maximum of about 5.7 m. Overall, the ice/water content of the top 15 m of frozen soil was usually <10%. The altitudinal limit of permafrost in the alpine steppe was about 5100, 5000, and 4950 m a.s.l. on south-, east-west-, and north-facing slopes, respectively. A permafrost map was constructed using the ARCGIS platform and topographic information from the TOPO 30 digital elevation model. Statistical analysis of the map revealed that permafrost is primarily distributed in the hilly/mountainous areas of Gaize, covering 51% of the study area. The area of permafrost in this map is considerably less than in the Permafrost Map of the Qinghai—Tibet Plateau drawn in 1996. Further analysis revealed that the large difference between the two maps could be attributed to both errors in the earlier mapping method and permafrost degradation.